Bankruptcy Law and Entrepreneurship Development: A Real Options Perspective - Lee, Seung-Hyun; Peng, Mike W.; Barney, Jay B. (Academy of Management Review, 2007)
We develop a real options perspective to explore how an entrepreneur-friendly bankruptcy law can encourage entrepreneurship development at the societal level. If bankrupt entrepreneurs are excessively punished for failure, they may let inherently high-risk but potentially high-return opportunities pass. We suggest that a more entrepreneur-friendly bankruptcy law, informed by a real options logic, can encourage more active and vibrant entrepreneurship development. We also discuss the implications of the role of venture capital and stigma in the effectiveness of an entrepreneur-friendly bankruptcy law.